A review of nutritional recommendations for scuba divers - Rhiannon J. Brenner; Kiran A. Balan; Marie P. L. Andersen; Emmanuel Dugrenot; Xavier C. E. Vrijdag; Hanna Van Waart; Frauke Tillmans (Taylor & Francis Group, 2024)
Background Scuba diving is an increasingly popular activity that involves the use of specialized equipment and compressed air to breathe underwater. Scuba divers are subject to the physiological consequences of being immersed in a high-pressure environment, including, but not limited to, increased work of breathing and kinetic energy expenditure, decreased fluid absorption, and alteration of metabolism. Individual response to these environmental stressors may result in a differential risk of decompression sickness, a condition thought to result from excess nitrogen bubbles forming in a diver's tissues. While the mechanisms of decompression sickness are still largely unknown, it has been postulated that this response may further be influenced by the diver's health status. Nutritional intake has direct relevancy to inflammation status and oxidative stress resistance, both of which have been associated with increased decompression stress. While nutritional recommendations have been determined for saturation divers, these recommendations are likely overly robust for recreational divers, considering that the differences in time spent under pressure and the maximum depth could result nonequivalent energetic demands. Specific recommendations for recreational divers remain largely undefined.Methods This narrative review will summarize existing nutritional recommendations and their justification for recreational divers, as well as identify gaps in research regarding connections between nutritional intake and the health and safety of divers.Results Following recommendations made by the Institute of Medicine and the Naval Medical Research Institute of Bethesda, recreational divers are advised to consume ~170-210 kJ·kg−1 (40-50 kcal·kg−1) body mass, depending on their workload underwater, in a day consisting of 3 hours' worth of diving above 46 msw. Recommendations for macronutrient distribution for divers are to derive 50% of joules from carbohydrates and less than 30% of joules from fat. Protein consumption is recommended to reach a minimum of 1 g of protein·kg−1 of body mass a day to mitigate loss of appetite while meeting energetic requirements. All divers should take special care to hydrate themselves with an absolute minimum of 500 ml of fluid per hour for any dive longer than 3 hours, with more recent studies finding 0.69 liters of water two hours prior to diving is most effective to minimize bubble loads. While there is evidence that specialized diets may have specific applications in commercial or military diving, they are not advisable for the general recreational diving population considering the often extreme nature of these diets, and the lack of research on their effectiveness on a recreational diving population.Conclusions Established recommendations do not account for changes in temperature, scuba equipment, depth, dive time, work of breathing, breathing gas mix, or individual variation in metabolism. Individual recommendations may be more accurate when accounting for basal metabolic rate and physical activity outside of diving. However, more research is needed to validate these estimates against variation in dive profile and diver demographics.